PENGARUH PENGGUNAAN PASIR KUARSA PADA LASTON AC-WC SEBAGAI PENGGANTI AGREGAT HALUS - Gayuh Bintang Ramadhan; Latif Budi Suparma (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2018)
Abstract Vehicle loads and high traffic growth nowdays lead to increased traffic loads on pavement that will accelerate the occurrence damage of pavement layer. Based from the natural resources of quartz sand was need to research quartz sand. Conducted test in this research were Marshall tests, immersion, and indirect tensile strength test to determined the durability of asphalt concrete mixture with optimum bitumen content after 5 variations were made in this research. The variations are V1, V2, V3, V4, and V5. The variations of quartz sand content that made based on the weight percentage on each aggregate filter numbers. The durability of the asphalt concrete mixture was seen from the value result of Marshall test, immersion test, indirect tensile strength test, residual strength index, and tensile strength ratio. The results show that Marshall stability value has decreased stability value in succession after immersion test. The indirect tensile strength results shows the tensile value performed on Un-Condition and Condition. The stability value of the indirect tensile strength Condition indicates a consecutive decrease due to immersion. Keywords: Marshall tests, indirect tensile strength test, immersion, quartz sand, residual strength index  Abstrak Pembebanan dan pertumbuhan lalu lintas yang tinggi menyebabkan bertambahnya beban lalu lintas pada konstruksi jalan yang akan mempercepat terjadinya kerusakan pada lapisan jalan raya. Dilihat dari sumber daya alam pasir kuarsa yang ada, maka perlu adanya penelitian tentang pasir kuarsa. Pengujian yang dilakukan dalam penelitian ini adalah uji Marshall, immersion, dan indirect tensile strength test untuk mengetahui durabilitas campuran beton aspal dengan KAO setelah dibuat 5 variasi secara berturut-turut pada campuran V1, V2, V3, V4, dan V5. Variasi kadar pasir kuarsa tersebut dibuat berdasarkan persentase berat pada setiap nomor saringan pada agregat halus. Durabilitas campuran beton aspal dilihat dari nilai hasil uji Marshall, immersion, indirect tensile strength test, indeks kekuatan sisa, dan rasio kuat tarik. Hasil pengujian menunjukkan nilai stabilitas Marshall mengalami penurunan nilai stabilitas secara berturut-turut setelah uji perendaman. Pengujian indirect tensile strength menunjukkan nilai tarik dilakukan pada Un-Condition dan Condition. Nilai stabilitas pada indirect tensile strength Condition mengalami penurunan berturut-turut akibat perendaman. Kata-kata kunci: uji Marshall, indirect tensile strength, immersion, pasir kuarsa, indeks kekuatan sisa